PEMANFAATAN LAHAN TERGENANG AKIBAT BANJIR ROB DI KELURAHAN DEGAYU KECAMATAN PEKALONGAN UTARA KOTA PEKALONGAN UNTUK BUDIDAYA IKAN KAKAP PUTIH - Fahrurrozi, Ashari; Syakirin, M. Bahrus; Linayati, Linayati; Rabbani, Nauval; Syamsuddin, Muhammad Dicky; Ikhsan, Mauliddin Khoerul (Jurnal Abdi Insani, 2024)
Degayu Village is one of the coastal areas affected by tidal flooding, which has closed most of the areas in the area. The surrounding community felt various losses, such as loss of jobs, housing and residence. So far, community land covered by water has not been utilized properly. An alternative solution of sea bass aquaculture could be the answer, because the advantages of sea bass make it possible to cultivate it in this location. Therefore, this community service aims to provide alternative solutions for utilizing flooded land. So that people can carry out cultivation activities independently and profitably. This community service activity method is carried out through counseling and providing demonstration plots, using step net cages as containers and sea bass for biota aquaculture. The results of the activity showed good understanding from the participants after the counseling was carried out with a percentage increase in understanding of 53.3%. Apart from that, this activity is really needed by the community which can be seen from the enthusiasm of the questions asked as well as the readiness to install equipment for the plot demonstration. The results of one week's rearing of sea bass aquaculture also showed good conditions. This condition can be seen from the growth of cultivated biota and the healthy physical condition of the fish. The conclusion of this service is that it is effective because it can provide knowledge and alternative efforts to participants regarding sea bass aquaculture.